2022
DOI: 10.1002/cncr.34350
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life data on treatment and outcomes in advanced ovarian cancer: An observational, multinational cohort study (RESPONSE trial)

Abstract: BACKGROUND:This study aimed to describe the treatment strategies and outcomes for women with newly diagnosed advanced highgrade serous or endometrioid ovarian cancer (OC). METHODS: This observational study collected real-world medical record data from eight Western countries on the diagnostic workup, clinical outcomes, and treatment of adult women with newly diagnosed advanced (Stage III-IV) high-grade serous or endometrioid OC. Patients were selected backward in time from April 1, 2018 (the index date), with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…The low numbers of patients receiving standard of care therapy and the high percentage of dose reduction or early dose interruption is in contrast with younger epithelial ovarian cancer patients. Treatment efficacy rates and survival percentages are modeled off clinical trials comprised primarily of patients under the age of 75, with high treatment completion rates and low–moderate dose reduction rates [ 12 ]. This emphasizes that patient selection for treatment is clinically very challenging and is an area where improvement and ongoing research are required.…”
Section: Discussionmentioning
confidence: 99%
“…The low numbers of patients receiving standard of care therapy and the high percentage of dose reduction or early dose interruption is in contrast with younger epithelial ovarian cancer patients. Treatment efficacy rates and survival percentages are modeled off clinical trials comprised primarily of patients under the age of 75, with high treatment completion rates and low–moderate dose reduction rates [ 12 ]. This emphasizes that patient selection for treatment is clinically very challenging and is an area where improvement and ongoing research are required.…”
Section: Discussionmentioning
confidence: 99%
“…The RESPONSE trial is an observational, multinational cohort study that collected real-world medical record data from eight Western countries on the diagnostic workup, clinical outcomes, and treatment strategies for women with newly diagnosed advanced high-grade serous or endometrioid ovarian cancer [ 22 ]. A clinical trial at the Mayo Clinic aims to identify candidate biomarkers for early detection and chemotherapy treatment response in high-grade serous cancer (HGSC) [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Furthermore, the RESPONSE trial, an observational, multinational cohort study, aimed to describe the treatment strategies and outcomes for women with newly diagnosed advanced high‐grade serous or endometrioid ovarian cancer. The study collected real-world medical record data on the diagnostic workup, clinical outcomes, and treatment strategies for ovarian cancer from eight Western countries [ 22 ]. In addition, a clinical trial at the Mayo Clinic aims to identify candidate biomarkers for early detection and chemotherapy treatment response in HGSC.…”
Section: Reviewmentioning
confidence: 99%
“…The most lethal gynecologic carcinoma is ovarian cancer. This cancer has a 5-year survival rate of ~45%, making it the fourth most common cancer with regards to mortality among Western nations [1][2][3]. The identification of molecular targets could aid in developing pharmacologic therapies to improve the prognosis for ovarian cancer [4].…”
mentioning
confidence: 99%
“…Selective GPER agonists and antagonists have recently been discovered to differentiate GPER-mediated estrogen activity from that of ER [10][11][12] . Consequently, G-1 1-[4-(6-bromobenzo [1,3]dioxol-5yl)-3A, 4,5, 9B, tetrahydro-3H cyclopenta[c] quinolin-8-yl]-ethanone has been recently demonstrated to be a GPER agonist [10]. Previous studies have shown that G-1 is a high-affinity, nonsteroidal, and selective GPER agonist [10,11].…”
mentioning
confidence: 99%